Pelvic Floor Symptoms and Spinal Curvature in Women - Meyer, Isuzu (Female Pelvic Med Reconstr Surg, 2016)
OBJECTIVES: To characterize the association between thoracic (T) and lumbar (L) spinal curvature and pelvic floor (PF) symptoms (pelvic organ prolapse [POP], urinary incontinence [UI], fecal incontinence [FI]). METHODS: Of women undergoing a bone mineral density scan from 1/2007 to 10/2010, patients who completed PF symptom questionnaires and had T and/or L spine radiographs or computerized tomography (CT) exams within 3 years of questionnaire completion were included in this study. The spine angles were measured using the Cobb angle method. The T and L curvature were categorized as hypo-kyphosis (<20°), normal thoracic kyphosis (20–40°), hyper-kyphosis (>40°), hypo-lordosis (<40°), normal lumbar lordosis (40–70°), and hyper-lordosis (>70°). The presence and type of UI were identified with the 3 Incontinence Questionnaire and FI with the Modified Manchester Questionnaire. POP was defined as a positive response to the presence of a bulge question from the PF Distress Inventory-20. RESULTS: Of 1665 eligible women, 824 and 302 (mean age 64±10 for both) had T and L spine images, respectively. No differences in PF symptoms were observed in the T or L spine groups categorized by hypo-, normal, and hyper-kyphosis/lordosis except for urgency UI being more prevalent in the hypo-lordosis group (p=0.01). However, upon further characterization using logistic regression, no association was noted between PF symptoms and T or L spine angles; no differences in the mean angles were found between women with versus without PF symptoms (p≥0.05). CONCLUSIONS: The current study shows that the thoracic and lumbar spinal curvature is not associated with the presence of pelvic floor symptoms.